Chemostratigraphy of some key European Frasnian-Famennian boundary sections (Germany, Poland, France) - Pujol, Frédéric (Karlsruher Mineralogische und Geochemische Hefte, 2005)
This study aimed to put constraints on regional and/or global environmental changes, which took place during the Frasnian-Famennian transition by using a geochemical multiproxy approach. The investigation of several key European Frasnian-Famennian boundary sections brings new geochemical evidences which emphasize the role of tectono-magmatic processes, like volcanism, hydrothermalism and major tectonic movements in the development of the particularities of the Kellwasser Horizons deposited close to the southern shores of Laurussia and the northern parts of Gondwana.